2022
DOI: 10.1111/1440-1681.13698
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects and mechanisms of action of resveratrol on polycystic ovary syndrome: A comprehensive systematic review of clinical, animal and in vitro studies

Abstract: Polycystic ovary syndrome (PCOS) is one of the most important and common polygenic endocrine disorders among women of reproductive age. Resveratrol, a natural phenol, is involved in various biological activities, including antioxidant, antiseptic, anti‐inflammatory, anti‐ageing and anti‐cancer effects. This systematic review aimed to investigate the therapeutic effects and mechanisms of actions of resveratrol in PCOS. The present study was conducted according to the guidelines of the Preferred Reporting Items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…OS in patients with PCOS may be associated with several diseases [ 34 , 35 ]. A few antioxidants can ameliorate PCOS through reducing OS, such as Tempol [ 36 ], Kelulut honey [ 37 ], Standardised Aronia melanocarpa [ 38 ], astaxanthin [ 39 ], resveratrol [ 40 ], and N-acetyl cysteine [ 41 ]. Besides, silibinin [ 42 ] and vitamin E supplementation [ 43 ] as well as melatonin and/or magnesium supplementation [ 44 ] also ameliorate PCOS by reducing the level of OS.…”
Section: Discussionmentioning
confidence: 99%
“…OS in patients with PCOS may be associated with several diseases [ 34 , 35 ]. A few antioxidants can ameliorate PCOS through reducing OS, such as Tempol [ 36 ], Kelulut honey [ 37 ], Standardised Aronia melanocarpa [ 38 ], astaxanthin [ 39 ], resveratrol [ 40 ], and N-acetyl cysteine [ 41 ]. Besides, silibinin [ 42 ] and vitamin E supplementation [ 43 ] as well as melatonin and/or magnesium supplementation [ 44 ] also ameliorate PCOS by reducing the level of OS.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review [ 93 •], which considered both in vitro studies and animal or human models of PCOS, it has been highlighted that resveratrol supplementation could be effective in reducing IR, improving dyslipidemia, ovarian morphology as well as anthropometric indices, regulating reproductive hormones and reducing inflammation and oxidative stress, influencing biological pathways.…”
Section: Adjuvant Nutraceutical and Pharmacological Treatmentmentioning
confidence: 99%
“…In DHEAinduced PCOS rats, it was testedat the dose of 20 mg/kg/day, and the study results reveal that it significantly decreases LH/FSH, TNFα, atretic follicles, Graafian follicles, and maintains folliculogenesis. 15 Rhamnocitrin is a flavonoid present in several medicinal herbs, has demonstrated anti-inflammatory, anti-apoptotic, and antioxidant activities. In letrozole-induced PCOS rats, rhamnocitrin was given at the dose of 5 mg/kg/day and it was reported that it ameliorates PCOS by reducing body weight, ovarian weight, improves ovarian structure and reduces fibrosis.…”
Section: Phytoconstituents In Pcosmentioning
confidence: 99%